1993
DOI: 10.1088/0953-8984/5/18/026
|View full text |Cite
|
Sign up to set email alerts
|

Optical properties of guanidinium aluminium sulphate hexahydrate (GASH)

Abstract: Far-infrared reflection spectra were determined, for the first time, for single crystals of guanidinium aluminium sulphate hexahydrate (GASH) and its solid solution for 5 mol.% chromium isomorph (GCSH). The infrared active transversal and associated longitudinal phonon frequency and the dielectric permittivity functions for E//C and E perpendicular to C have been determined using both Kramers-Kronig analysis and a fitting procedure based on a four-parameter model. The indices of refraction were also measured u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…1 -3 Complexes of guanidinium ions have a wide range of applications such as destruction of aqueous wastes of biotic origin, rocket propellant formulations, explosives, etc. 5,6 Despite the range of applications, only a few vibrational spectroscopic studies on this family compounds have been carried out. 5,6 Despite the range of applications, only a few vibrational spectroscopic studies on this family compounds have been carried out.…”
Section: Introductionmentioning
confidence: 99%
“…1 -3 Complexes of guanidinium ions have a wide range of applications such as destruction of aqueous wastes of biotic origin, rocket propellant formulations, explosives, etc. 5,6 Despite the range of applications, only a few vibrational spectroscopic studies on this family compounds have been carried out. 5,6 Despite the range of applications, only a few vibrational spectroscopic studies on this family compounds have been carried out.…”
Section: Introductionmentioning
confidence: 99%
“…The crystal structure, vibrational spectroscopic studies and ferroelectric properties of some guanidinum metal sulphates have been reported in the literature [6][7][8]. Many guanidinuim based nonlinear optical crystals were grown and reported [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Guanidinium aluminum sulfate hexahydrate (C(NH 2 ) 3 Al(SO 4 ) 2 · 6H 2 O, GASH for short) is of significant due to its optical, ferroelectric, piezoelectric, dielectric, and other properties 1–4. It is useful for technical applications such as optoelectronic devices, semiconductor memory devices, and ferroelectric thin films.…”
Section: Introductionmentioning
confidence: 99%